2016
DOI: 10.1016/j.nicl.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Recreational marijuana use impacts white matter integrity and subcortical (but not cortical) morphometry

Abstract: A recent shift in legal and social attitudes toward marijuana use has also spawned a surge of interest in understanding the effects of marijuana use on the brain. There is considerable evidence that an adolescent onset of marijuana use negatively impacts white matter coherence. On the other hand, a recent well-controlled study demonstrated no effects of marijuana use on the morphometry of subcortical or cortical structures when users and non-users were matched for alcohol use. Regardless, most studies have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 60 publications
9
58
1
Order By: Relevance
“…This is consistent with our previous work suggesting that regionally specific differences between cannabis users and non-users are often inconsistent across studies and that some of the observed associations may actually be related to comorbid alcohol use [40]. The present results are also consistent with a recent study from a large consortium project that found no relationship between cannabis use and cortical GM ( N =466) [68] and a large twin study ( N =483) that found the association between cannabis use and GM volumes was explained by genetics rather than cannabis use [69]. While the analyses reported herein are consistent with the effects reported in studies with large sample sizes, future longitudinal studies will be important to clarify the effects of cannabis and alcohol use on brain structure.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our previous work suggesting that regionally specific differences between cannabis users and non-users are often inconsistent across studies and that some of the observed associations may actually be related to comorbid alcohol use [40]. The present results are also consistent with a recent study from a large consortium project that found no relationship between cannabis use and cortical GM ( N =466) [68] and a large twin study ( N =483) that found the association between cannabis use and GM volumes was explained by genetics rather than cannabis use [69]. While the analyses reported herein are consistent with the effects reported in studies with large sample sizes, future longitudinal studies will be important to clarify the effects of cannabis and alcohol use on brain structure.…”
Section: Discussionsupporting
confidence: 93%
“…Also, there are mark irregularities in the distributions of nissl granulation in the perikaryon and increased dark pyknotic nuclei, presence of dark neuron suggesting protein denaturation and neural degeneration as seen in group III of Cresyl Fast Violet stain. This agrees with the findings of previous studies on Cannabis who reported that Cannabis induce nervous tissue damage (Rapp et al, 2013;Jacobus et al, 2016;Orr et al, 2016). Administration of cannabis as reported by Imam et al (2017) observed that, the pyramidal cells at the internal pyramidal cell layer show some degree of retraction of processes, vacuolation of the surrounding neuropil of the pyramidal cells, and hyperchromatic and shrunken perikarya which are also similar to this study.…”
Section: Discussionsupporting
confidence: 93%
“…The evolving views on legalization of marijuana for recreational use in the USA, Canada, and various European countries has led to a growing interest in the long‐term effects of cannabis use on the integrity of human brain structures, especially in regions rich in cannabionoid CB1 receptors, including prefrontal cortex, hippocampus, amygdala, striatum, and cerebellum. Although there are now many studies using structural MRIs to evaluate the long‐term effects of cannabis use, the results have been inconsistent with early studies showing significant loss of gray and/or white matter (e.g., Battistella et al, ; Churchwell, Lopez‐Larson, & Yurgelun‐Todd, ) whereas more recent studies have failed to confirm this, possibly because of various comorbid factors (e.g., Weiland et al ), although one study of a large sample of users showed a correlation between cannabis use and white matter integrity and subcortical, but not cortical, morphometry (Orr, Paschall, & Banich, ).…”
Section: Introductionmentioning
confidence: 99%